PEMIKIRAN KALAM KIAI MUHAMMAD SAMI’UN PURWOKERTO DALAM NASKAH AQAID 50 The Islamic Theological Thoughts Of Kiai Muhammad Sami’un From Purwokerto In Text “Aqaid 50” - Umi Masfiah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
The study of Kiai Muhammad Sami’un’s thoughts in the text “Aqaid 50” has an important value as an effort to appreciate the work of local scholar. The text “Aqaid 50” contains the discussion of God’s and His apostle’s attributes: wajib (obligatory), mustahil (inadmissible), and jaiz (admissible). The attributes of Allah (the Most Glorified, the Most High) in the text “Aqaid 50” affirmed by the dalil aqli (rational arguments) in the form of evidence of the universe existence and the preposition of comparison with beings other than Allah who are ‘recency’ (huduts). This research is conducted through the study of critical discourse analysis. The results of the study show that the use of the dalil ‘aqli (rational arguments) to understand God’s attributes has a purpose to make the concept more easily understood substantially by community. The writing of the “Aqaid 50” aims to affirm the Ahl Sunnah wal Jamaah in the community. This text was written in Arab Pegon (Javanese texts written in Arabic script) in the 1930s. As far as the Islamic theological issues are concerned, Kiai Sami’un’s Islamic Theological (kalam) thought is similar to classical Islamic theology. In the present era, the type of Kalam thought or Islamic theology should be more transformative in which tauhid as the core of Kalam thought can be the spirit for every Moslem to be “the perfect man” (al-Insan al-Kamil) for the benefit of mankind.